GOSSYPIBOMA - CASE REPORT - Prgova, Biljana; Veljanovski, Dimitar; Dejanova Panev, Sandra; Kostova, Masha (Македонско лекарско друштво = Macedonian medical association, 2023)
Introduction. The term Gossypiboma is used to describe a retained surgical sponge after surgical procedure. It is an infrequent but serious surgical complication which is seldom reported because of the medicolegal implications. Its diagnosis is usually difficult because the clinical symptoms are nonspecific and the imaging findings are often inconclusive. Case presentation. We report a case of 68-year-old female who presented with acute pain abdomen and severe distention of abdomen. She had history of hernioplasty 1 year ago prior at another hospital. From clinical features the patient had discomfort in epigastrium, upper gastrointestinal symptoms and fever. On computed tomography (CT) and magnetic resonance (MRI) was seen abscess collection in upper abdomen, with visible inhomegenous spongeous mass, that did not exclude presence of foreign body. On exploratory laparotomy there was a lump in abdominal cavity, which confirmed the diagnosis of Gossypiboma. Discussion. Gossypiboma is an important topic, seldom reported because of the medicolegal issues and a significant embarrassment; it is considered by some authors as a severe postoperative iatrogenic complication. The reported estimate of retained surgical items is 1.32 per 10, 000 procedures and 0.3 to 1% of abdominal operationsIts clinicalpresentation is extremely variable. The standard treatment is laparotomy, surgical removal, and in some selected cases, laparoscopic and endoscopic removal can be performed. Conclusion. Gossypibomas are uncommon, mostly asymptomatic, and hard to diagnose. Gossypiboma is an unwanted and preventable complication that should be considered as a differential diagnosis for all mass lesions detected in the postoperative period. It is considered a serious medicolegal problem and, hence, should be prevented at all costs.